Building resilience to hazards in the water, sanitation, and hygiene (WASH) systems: a global review. - Tshuma, M.; Belle, J. A.; Ncube, A.; Nyam, Y. S.; Orimoloye, I. R. (International Journal of Environmental Health Research, 2024)
Building the resilience of communities is essential in achieving Sustainable Development Goals (SDG). Scientific research is crucial in identifying gaps in the development of WASH systems and the management of WASH-related hazards. The main purpose of this paper was to analyze the global research evolution on resilience and Water, Sanitation, and Hygiene (WASH) between the period 2003 and 2021. Bibliometric analysis was done through the analysis of research articles from the Web of Science and Scopus using R Package software A total of 110 articles were generated from the Web of Science and Scopus databases. The study revealed that there was very little research on WASH from 2003 to 2010 and a steady increase from 2011 to 2018 and a sharp increase from 2019 to 2020 with a slight drop in 2021. This paper, therefore, recommends more focused scientific research on WASH issues in Africa and Southern Africa in particular.